Kevin Hart's guide to black history [videorecording (DVD)] - Hart, Kevin, 1979-; Haddish, Tiffany, 1979-; Sidney, Saniyya; Yankovic, Al, 1959- (Screen Media, 2020)
Kevin Hart highlights the fascinating contributions of black history's unsung heroes in this entertaining and educational comedy special.